The Role of School Operators in Data and Information System Management and Service to Improve School Quality - Emelia Rosana (Indonesian Journal of Education (INJOE), 2022)
Education today requires a foundation that must be built, namely realizing its position as a producer of educational services. Schools must understand well the increasingly complex needs of society, especially following the very rapid development of IT information. The research with the title "the role of school operators in managing information data systems as quality assurance of education services has a problem formulation what is the role of school operators in managing information data systems as education quality assurance, the process of managing data and information systems as quality assurance, and What is the relationship between school operators and the process of managing data and information systems with the quality of education services. The purpose of this study was to determine the role of school operators in managing information data systems as a guarantee of the quality of education services, along with the relationship between school operators and the process of managing data and information systems with the quality of education services. The object of this research is focused on the role of school operators in managing information data systems as a guarantee of the quality of education services. This research is descriptive qualitative which describes based on what it is. The result of this research is that the operator's role in managing the information data system is an indicator of the quality of education services. The relationship between them is symmetrical because the task of the service does not rely on the operator alone